The Impact of Lending Growth and Financial Statistics on Bank Profitability : The Moderating Role of Credit Risk - Salsabila, Zahra; Rhamdani, Eka Wulan; Putri, Alfina Naufali; Komara, Acep (International Journal of Business, Economics, and Social Development, 2024)
The purpose of this study was to examine the effect of Lending Growth, BOPO, and CAR on Banking ROA with NPL as a moderating variable. The problem contained in this study is that there is a gap between the value of theory and the value of real practice based on the factors that create variations in ROA value. Indonesian banking companies for the period 2018-2022 published on the IDX website are used as the research population in this study. Selection of research samples through purposive sampling to obtain 19 companies. Panel Data Regression Analysis is a data analysis process that processes data using the Eviews 12 program. The level of loan, BOPO, and CAR are assumed to have an effect on bank profitability in this analysis. The effect of credit risk ratio amplifies the impact on the level of lending, BOPO, and CAR on profitability. The results of data analysis contain the statement that bank profitability can be influenced by lending and BOPO, but cannot be influenced by CAR. Similarly, the role of credit risk cannot moderate the effect of CAR on ROA but can weaken the effect of lending and BOPO on bank ROA.